On the transferability of snowmelt runoff model parameters: Discharge modeling in the Chandra-Bhaga Basin, western Himalaya - Vinze, Parul; Azam, Mohd. Farooq (Frontiers in Water, 2023)
Snowmelt runoff plays a major role in the glacierized and snow-covered basins in the western Himalaya. Modelling is the most helpful tool to quantify snowmelt contribution in mountainous rivers. However, the model calibration is very difficult because of the scarcity of ground observations in the Himalaya. We applied Snowmelt Runoff Model (SRM) in a reference catchment of Chhota Shigri Glacier in the Chandra-Bhaga Basin, western Himalaya. Three model parameters (temperature lapse rate and recession coefficients (x and y)) among the nine model parameters were constrained using extensive field observations while initial values of other parameters were adopted from previous studies and calibrated, and the model was calibrated and validated against the observed discharge data. The daily discharge was simulated over 2003-2018 for both Chhota Shigri Catchment and Chandra-Bhaga Basin using snow cover area (SCA), precipitation, and temperature as inputs. The simulated mean annual discharges were 1.2 ± 0.2 m3/s and 55.9 ± 12.1 m3/s over 2003-2018 for Chhota Shigri Catchment and Chandra-Bhaga Basin, respectively. The reconstructed discharge was mainly controlled by summer temperature and summer SCA in the Chhota Shigri Catchment and summer SCA and summer precipitation in the Chandra-Bhaga Basin. The decadal comparison showed an increase (11% and 9%) and early onset (10 days and 20 days) of maximum monthly discharge over 2011-2018 compared to 2003-2010 in both catchment and basin scales. The model output is almost equally sensitive to the ‘degree day factor’ and ‘runoff coefficient for snow' in the Chhota Shigri Catchment and most sensitive to the ‘runoff coefficient for snow' in the Chandra-Bhaga Basin. Though the SRM parameters were constrained/calibrated in a data-plenty reference catchment of Chhota Shigri Glacier, their application resulted in large discharge overestimation at the basin scale and were not transferable in the same basin i.e., Chandra-Bhaga Basin. Extreme care must be taken while using SRM parameters from other basins.